Petrophonics - Janzen, David; Martens, Reuben (Anthropologica, 2025)
Drawing from sound studies, energy humanities, and anthropology, this essay identifies a critical gap in the academic recognition of “petrophonics”—sonic and vibrational byproducts of fossil fuel dependency that pervade contemporary soundscapes—within sound and soundscape studies as well as the environmental and energy humanities, where such phenomena are often dismissed as “white noise” or background ambience. Through theoretical analysis and empirical observation, we attempt to define petrophonics as both an object of study and a framework for critical engagement. Focusing on traffic noise—the most accessible example of petrophonics—as a cultural and material phenomenon rather than a mere auditory background allows us to explain and propose a speculative definition of petrophonics, characterized by its materialist grounding in fossil fuel infrastructures and its capacity to exist independently of audibility. This essay concludes by emphasizing the political, temporal, and decolonial dimensions of petrophonics, advocating for an ethico-affective approach that foregrounds the relational and infrastructural realities of petromodernity. This framework invites scholars and practitioners to re-attune to the pervasive yet overlooked sounds of fossil fuel dependency and imagine alternative, post-petrocultural phonic worlds.